The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1063/1.1616638
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal and electrical properties of carbon nanotube polymer composites by magnetic field processing

Abstract: We show that the thermal and electrical properties of single wall carbon nanotube (CNT)-polymer composites are significantly enhanced by magnetic alignment during processing. The electrical transport properties of the composites are mainly governed by the hopping conduction with localization lengths comparable to bundle diameters. The bundling of nanotubes during the composite processing is an important factor for electrical, and in particular, for thermal transport properties. Better CNT isolation will be nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
236
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(252 citation statements)
references
References 19 publications
6
236
2
1
Order By: Relevance
“…The PNCs have attracted great attention due to their drastically enhanced properties [3][4][5]. For instance, thermally insulating polymers can be transformed into thermal conductors after reinforcing with carbon nanotubes (CNTs) [6][7][8]. Moreover, PNCs have demonstrated improved mechanical, gas barrier, solvent resistance, and flammability properties compared to the corresponding neat matrices [3,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…The PNCs have attracted great attention due to their drastically enhanced properties [3][4][5]. For instance, thermally insulating polymers can be transformed into thermal conductors after reinforcing with carbon nanotubes (CNTs) [6][7][8]. Moreover, PNCs have demonstrated improved mechanical, gas barrier, solvent resistance, and flammability properties compared to the corresponding neat matrices [3,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among these additives studied CNT may have the potential to improve the mechanical and thermal properties of MgB 2 wires since CNTs have been used as component for a number of composites to improve their mechanical properties. [17,18] Fosshein et al report an enhanced flux pinning in Bi 2 Sr 2 CaCu 2 O 8+x superconductors with embedded CNTs. [19] Yang et al found a significant enhancement in J c (H) for high temperature superconductor by introducing nanorods as columnar pinning centers in to the composites.…”
mentioning
confidence: 99%
“…The alignment of CNTs in a polymer matrix using magnetic field was reported previously [5][6][7][8]. We conducted comparative experiments using dispersed and non-dispersed CNTs.…”
Section: Alignment Of Cntsmentioning
confidence: 99%
“…Many studies have been reported on the alignment of CNTs by magnetic methods [4][5][6][7][8]. High magnetic fields made it possible to visualize magnetic effects on diamagnetic materials such as CNTs [9].…”
Section: Introductionmentioning
confidence: 99%